(untitled) (Al-Qamar, 2022)
The Quran is the most Read Book in the world. Revealed by the Allah to Holy prophet Muhammad, and the Quran is the source of guide for all human being .there are blessings, promises, warning, rules, exhortation, orders, prohibitions and Examples .The holy Quran called peoples to Monotheism and Reject polytheism in a variety of ways .it is known the Examples in the holy Quran is one of the Methods has great impact on persuasive and influential events. This Research article Explains and analyze about the importance and method of Examples of Quran for inviting people to towhead denying polytheism.